The Influence of Intensity Use of Tiktok Social Media on Student Social Interaction - Br.Ginting, Novia Rizki Ramadhani; Wijaya, Candra; Suhairi (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims to determine the effect of the intensity of the use of social media tiktok on the social interaction of MA al-jam'iyatul washliyah tembung students. Quantitative research is a type of research that aims to collect information from a sample through answers to questions given to individuals or groups who generally use a questionnaire as a data collection tool. The results of the study showed that the intensity of social media use, Tiktok, averaged scores, and students' social interaction with an average score. There is an influence of the intensity of the use of social media Tiktok on social interaction of students. The Intensity Score of Use of Social Media Tiktok (X) as many as 17 people (42.5%) is below the interval class average and as many as 10 people (25%) are on average interval class average and as many as 23 people (57.5%) above the average. Based on the data above, the Tiktok Social Media Use Intensity score (X) is generally above the average, the Social Interaction Score of Students (Y) of 19 people (47.5%) is below the interval class average and as many as 7 people (17.5%) are in the average interval class and as many as 14 people (35%) are above average. The intensity of Tiktok Social Media Use (X) has an influence on Student Social Interaction (Y) of 36%.